2019
DOI: 10.1007/s11934-019-0933-1
|View full text |Cite
|
Sign up to set email alerts
|

Female Urethral Strictures: Review of Diagnosis, Etiology, and Management

Abstract: Purpose of ReviewIn this review, we describe the incidence, diagnosis, and management of urethral strictures in women. Recent Findings Definitive repair of urethral strictures in women traditionally utilizes vaginal and labial flaps. Oral mucosal buccal graft urethroplasty also has high success rates, with larger series demonstrating feasibility and durability. Summary Urethral strictures in women are very rare. When they do occur, they are often difficult to diagnose, requiring a high index of suspicion. Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
(42 reference statements)
0
22
0
3
Order By: Relevance
“…Injury to the urethral epithelium may result in healing by scarring and subsequent formation of a stricture 3 . The patients may present with LUTS, recurrent urinary tract infections (UTIs), overflow incontinence of urine, urethral pain, and/or high postvoid residual urine (PVR) 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to the urethral epithelium may result in healing by scarring and subsequent formation of a stricture 3 . The patients may present with LUTS, recurrent urinary tract infections (UTIs), overflow incontinence of urine, urethral pain, and/or high postvoid residual urine (PVR) 4 …”
Section: Introductionmentioning
confidence: 99%
“…3 The patients may present with LUTS, recurrent urinary tract infections (UTIs), overflow incontinence of urine, urethral pain, and/or high postvoid residual urine (PVR). 4 Precise diagnosis of FUS demands a high index of suspicion because of its uncommon nature, nonspecific presentation, and absence of a standardized definition as well as diagnostic criteria. It is, therefore, imperative to perform a battery of tests as the diagnosis cannot be based reliably on just one modality of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal flap and buccal mucosal graft urethroplasty were more reported and used for female urethral reconstruction, while these techniques are more suitable for female urethral stricture and small urethral loss. For long urethral defect or proximal urethral injuries bladder wall flaps can be adopted for urethroplasty [ 7 9 ].The female urethral replacement is mainly accomplished by anterior bladder wall (Tanagho) tube or tubularization of vaginal mucosa [ 10 ]. Tanagho was first to bring up the technique of reconstructing bladder neck with tubular anterior bladder flap in 1981 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urethral stricture in and of itself is most notably thought to be secondary to an iatrogenic or traumatic history often found in patients with a history of pelvic fracture, childbirth, prolonged catheterization or status-post repair for urethral diverticulum, incontinence, a fistula or even prior treatments for urethral stricture that may worsen symptoms [134,139]. In a recent study the most common causes of urethral stricture in females was found to be prior urethral instrumentation, traumatic catheterization and history of traumatic childbirth [140].…”
Section: Urethral Stricture Diseasementioning
confidence: 99%